Respuesta :

Answer:

The expression that could be used is (-4)(3) + (-4)([tex]\frac{1}{4}[/tex])B

Step-by-step explanation:

Let us revise the distributive property:

The product of a number and the sum of 2 other numbers equal to the sum of the products of the number with the other 2 numbers

  • a(b + c) = ab + ac

We will use this rule to solve the question

∵ The product of -4 and 3[tex]\frac{1}{4}[/tex] = -4 × 3[tex]\frac{1}{4}[/tex]

→ We can right 3[tex]\frac{1}{4}[/tex]  as (3 + [tex]\frac{1}{4}[/tex] )

3[tex]\frac{1}{4}[/tex] = (3 + [tex]\frac{1}{4}[/tex] )

∴ -4 × 3[tex]\frac{1}{4}[/tex] = -4(3 + [tex]\frac{1}{4}[/tex] )

→ By using the rule above

∵ -4(3 + [tex]\frac{1}{4}[/tex] ) = (-4)(3) + (-4)([tex]\frac{1}{4}[/tex])

∴ -4 × 3[tex]\frac{1}{4}[/tex]  = (-4)(3) + (-4)([tex]\frac{1}{4}[/tex])

The expression that could be used is (-4)(3) + (-4)([tex]\frac{1}{4}[/tex])

ACCESS MORE